Barriers and facilitators for treatment-seeking among women with genital fistula: a facility-based qualitative study in Bangladesh - Kanako Kon; Atsuko Imoto; Sabina Faiz Rashid; Ken Masuda (Tropical Medicine and Health)
Abstract Background Women living with genital fistula often endure prolonged suffering and face multiple barriers to accessing treatment. Bangladesh’s government has enhanced referral mechanisms, enabling case detection in communities and facilitating surgical interventions at medical college hospitals through nationwide initiatives. However, research on barriers and facilitators for fistula treatment in Bangladesh remains limited. Detailed insights into treatment-seeking paths with time sequences are scarce. This study aimed to explore facilitators and barriers to completing fistula treatment with the description of treatment-seeking paths. This study is important to assist with future policy and program strategies for fistula treatment. Methods A facility-based qualitative study was conducted at Dhaka Medical College Hospital, Dhaka, Bangladesh. Data were collected from February to May 2024 through 18 in-depth interviews (IDIs) with in-patients, five IDIs with families, and 11 key informant interviews with health service providers. Participants’ treatment-seeking paths were described chronologically and identified patterns of treatment-seeking paths. Thematic analysis, guided by the Partners for Applied Social Sciences model for health-seeking behavior and access to care, was used to analyze case histories. Results The average duration of treatment-seeking by the women was 39 months, with a maximum of 22 years. Women with fistula often sought care at multiple facilities (up to eight), suspended treatment, and encountered systemic obstacles that delayed treatment. Key barriers included scarce information on illness and treatment in the community, less decision-making power, failure of medical communication, and systemic failures in cost, treatment, and referral systems. Facilitators that motivated women to complete treatment included informal peer support through shared treatment experiences and emotional, physical, and financial support. Conclusions Analysis of treatment-seeking paths revealed the absence of standardized treatment routes for women with fistula. To ensure effective care, raising societal awareness about fistula, improving treatment and referral systems, enhancing medical communication, and providing peer and emotional support are strongly recommended.